Tatalaksana Primary Biliary Cirrhosis - Pratama, Hamzah (PT. Kalbe Farma Tbk., 2017)
Primary biliary cirrhosis (PBC) merupakan penyakit inflamasi/ peradangan hati kronik, progresif lambat, autoimun. Penyakit ini mempunyai karakteristik antimitochondrial antibodies (AMA) dengan titer tinggi dan penghancuran duktus intrahepatik berukuran kecil sampai sedang yang dimediasi imun. Mekanisme patogenik PBC masih belum jelas. Berbagai pendekatan diagnosis disebutkan dalam panduan American Association for Study of Liver Diseases. Pilihan terapi pertama saat ini adalah UDCA (Ursodeoxycolic acid) 13-15mg/kg dan terapi simptomatik.Primary biliary cirrhosis (PBC) is a slowly progressive, autoimmune chronic inflammatory disease of the liver with high titers of antimitochondrial antibodies (AMA) and immune-mediated destruction of small to medium size intrahepatic ducts. The pathogenic mechanisms of PBC is still not clearly known. Various approaches have been mentioned in the diagnosis guideline by the American Association for the Study of Liver Diseases. The first therapeutic option is UDCA (Ursodeoxycolic acid) 13-15mg/ kg/ day and symptomatic treatment.Â